2021
DOI: 10.3390/agronomy11091851
|View full text |Cite
|
Sign up to set email alerts
|

Do Water and Nitrogen Management Practices Impact Grain Quality in Maize?

Abstract: Concomitantly pursuing superior maize (Zeamays L.) productivity with grain quality is essential for food security. Therefore, this study provides a meta-analysis of 21 studies assembled from the scientific literature to tackle the effect of the two most limiting factors for maize production, water and nitrogen (N), and their impacts on grain quality composition, herein focused on protein, oil, and starch concentrations. Water stress levels resulted in erratic responses both in direction and magnitude on all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 59 publications
(84 reference statements)
0
10
0
Order By: Relevance
“…In maize, effective nitrogen application improves quality characteristics such as grain protein content (Amanullah et al, 2009) and affects grain protein concentration more consistently, with a large effect size for protein as N fertilizer levels rise (Correndo et al, 2021). However, the low and high N dose rates can also affect the quality of maize.…”
Section: Introductionmentioning
confidence: 99%
“…In maize, effective nitrogen application improves quality characteristics such as grain protein content (Amanullah et al, 2009) and affects grain protein concentration more consistently, with a large effect size for protein as N fertilizer levels rise (Correndo et al, 2021). However, the low and high N dose rates can also affect the quality of maize.…”
Section: Introductionmentioning
confidence: 99%
“…This result demonstrates a greater flux of NO 3 − in the soil-plant profile during this period in NI + NFM treatment. Meta-analysis of Correndo et al (2021) revealed that N fertilization not only increased grain yield but also grain protein content. The adequate proportion, quantity, and timing of soil available NO 3 − that influence maize production and grain protein content should be followed up in future research.…”
Section: Discussionmentioning
confidence: 99%
“…However, to scavenge the accumulation of these ROS, the plant starts to produce several enzymatic and non-enzymatic antioxidants including peroxidase (POX), superoxide dismutase (SOD), catalase (CAT), carotenoids, polyphenols, glutathione and ascorbate ( Shafiq, Akram & Ashraf, 2019 ). Maize yield, oil and starch contents percentage were reported to be reduced under water stress conditions however the protein contents were getting increased ( Correndo et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%